Wounded Warriors of the Future Disability Hierarchy in Avatar and Source Code. Issue 4 (1st October 2020) - Schalk, Sami
Abstract : The article analyzes the representation of disabled veterans in James Cameron's Avatar and Duncan Jones's Source Code . The argument is that these two films use the figure of the heroic, technologically enhanced, white disabled veteran man to alleviate cultural anxieties, fears, and guilt about veterans and disabled people in the contemporary United States. In doing so, however, Avatar and Source Code perpetuate a disability hierarchy that reinforces a variety of oppressive cultural norms. The article, therefore, demonstrates how the films reflect the differential valuation and treatment of different kinds of disabled people in American culture at large via the genre of science fiction and its technological imaginative possibilities.